ROAD DRAINAGE SYSTEM DESIGN EVALUATION (CASE STUDY OF PRAMUKA ROAD, BANJARBARU CITY) - Secondhanti, Firstyarinda Poppy; Fitriati, Ulfa (Universitas Lambung Mangkurat, 2024)
The drainage canal development project discussed is one of the projects undertaken by the Public Works and Spatial Planning Office of the City of Banjabaru. This drainage is located along Jalan Pramuka, North Loktabat. As a result of changes to the urban planning system in the city of Banjabaru, the work on improving the city's drainage system on the surrounding roads began. Many things cause an increase in the flow coefficient, which can trigger sedimentation in drainage channels and even runoff in the following years. The causes include the development and increasing density of the urban area of Banjarbaru and the bad habits of the people, such as throwing garbage in the canal.This research aims to redesign the drainage system in order to obtain a drainage network system that is more optimal in terms of environment, materials, and costs. This research was conducted by analyzing the design flood discharge at the location of the Banjarbaru City Urban Drainage System Development Project, calculating the existing drainage system calculation analysis, and evaluating a more optimal and economical drainage system design that could be suggested.Data analysis was carried out by hydrological analysis and hydraulic analysis. Furthermore, to process the data obtained, several calculation steps are carried out, such as processing daily rainfall data, frequency analysis, and discharge calculations. Through these calculations, the design discharge Qr 2 years is 0.0733 m3/second, Qr 5 years is 0.1075 m3/second, Qr 10 years is 0.3280 m3/second, Qr 15 years is 0.3599 m3 /second, Qr 20 Years of 0.3827 m3/second. The cross-sectional size of the box culvert used was 50 x 40 x 100 x 15 cm with a discharge capacity of 0.4148 m3/second, while the size of the masonry used was 30 x 40 x 40 with a discharge capacity of 0.4367 m3/second. Keywords: discharge plan, highway drainage, discharge capacity, runoff, channels